Motivasi Konsumen Dalam Mengkonsumsi Susu Sapi Murni Di Warung " Marko Milk " Dan " Julia Gizi " - Wahyu Wira Maulana (Fakultas Pertanian UMY, 2014)
Consumer Motivation In Whole Milk In "Marko Milk" and "Julia Gizi". 2013. WAHYU WIRA MAULANA (Thesis guided by SRIYADI & DIAH RINA KAMARDIANI). The purpose of this study are to determine the profile of stalls and constomer in general, knowing the consumer motivation in whole milk consuming, and knowing the differences of consumer motivation at "Marko Milk" and "Julia Gizi". This study uses descriptive and analytical techniques using t test method. The results of this study show those consumers who come in the shop "Marko Milk" and "Julia Gizi" the majority of the male students, aged 17-35 years, and income 500.000 <Rp.1.500.000. Consumers are motivated by the attributes of taste, price, menu, service, cleanliness, safety, practicality, benefit, comfort, amenities, distance, and follow your friends to consume milk in both the stalls. Consumers are turning to whole milk because of the trend and begin to realize the health of the body. At the service attributes and facilities or significant differences, where the service provided "Julia Gizi" there is a difference in serving consumers with fewer attractions, as well as the facilities provided stalls whole milk "Milk Marko" like Wi-Fi, TV, toilet, and washtafel. This is not found together in both these stalls. With the advantages of each stall two stalls are expected to maintain and develop the whole milk stall, can also influence people to want to come back to consume whole milk to understand its benefits.